Laser Treatment of Darier Disease: Report of Two Cases and Systematic Review of the Literature - O’Brien, Kathleen F; Fricke, Michelle A; Kent, Rhett A; DeKlotz, Cynthia Marie Carver (Journal of Lasers in Medical Sciences, 2020)
Introduction: Darier Disease (DD) is a chronic disease with high morbidity and limited treatment options. Laser efficacy in the treatment of DD remains understudied. Methods: A literature search conducted between 07/21/2017 and 05/05/2018 identified all original cases of DD treated with laser therapy. Results: Outcomes from 24 patients were reviewed, 22 patients were identified in the literature and 2 cases are included from our institution. Five types of lasers were identified [CO2 laser, Er:YAG laser, pulse dye laser [PDL], diode laser, erbium-doped fiber laser], with CO2 (46%) and PDL (42%) being the most common. Seventy-nine percent of patients were treated with more than one procedure (average, 3 procedures). The estimated body surface treated with each session ranged from 5%-50%. The most common adverse events came from CO2 and Er: YAG lasers and included dyspigmentation, pain, and post-laser erythema and edema. The time to response (mode, 1 month) was only reported in half of the studies. Conclusion: Laser treatments appear to be a promising alternative to standardized therapies in DD.